The Fatty Acid Composition of Excreta of Broiler Chickens Fed Different Dietary Fatty Acids - Kanakri , Khaled; Carragher, John; Hughes, Robert; Muhlhausler, Beverly; Koning, Carolyn de; Gibson, Robert (International Journal of Poultry Science, 2017)
Background and Objective: Excreted fatty acids represent the net result of fat digestion, absorbtion and bioconversion by chickens or their intestinal microbiome and thus provide information on the capacity of the birds to utilize different fat types. This study aimed to clarify the relationship between the fatty acid profile of diet and excreta in broiler chickens. Materials and Methods: Male Cobb 500 broilers (n = 240) were fed (ad libitum) one of 6 different diets supplemented with 4% (w/w) beef tallow, flaxseed, corn, macadamia, canola or coconut oils (4 replicate pens/treatment) from hatching day. At day-40 post-hatch, excreta samples were collected for fatty acids analysis. Results: Significant positive linear correlations (R = 0.82-0.99) were found in the fatty acid content of diets and excreta for all fatty acid groups in all treatments. Comparing the individual fatty acid content of diet and excreta suggested that the broilers preferentially utilized (in decending order, if present) omega-3 polyunsaturated fatty acids, omega-9 and omega-7 monounsaturated fatty acids and most saturated fatty acids (except C16:0 and C18:0), but the omega-6 polyunsaturated fatty acids were under utilized even when they were the most abundant. Conclusion: Fat sources which are high in the C16:0, C18:0 and omega-6 fatty acids may not be ideal for broiler feed formulations for nutritional and economical reasons.